Manufurrt: A Feasibility Investment and Operational Desktop Calculator - Nugroho, Handi Wilujeng; Hamidi, Kurniawan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The prospect of success of a manufacturing project is determined by the results of feasibility tests such as investment and operations. In its implementation, the feasibility test is often constrained by several things such as data entry errors, calculation errors, and a long calculation time. The ideal solution that can be used to solve these three obstacles is to design an offline and stand-alone desktop-based feasibility calculation application. This research uses the SDLC Waterfall method and User Acceptance Test (UAT) based on questionnaires and scenario tests. In the design and coding completion phase, the SDLC waterfall approach is combined with generative AI to speed up the application design time. As a result, a calculation application named Manufurrt has been created with an interactive executable file format and is able to provide the same calculation results between the expected spreadsheet and the real calculation results from the application.